Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1996
DOI: 10.1115/96-gt-131
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Airblast Sprays Under High Ambient Pressure Conditions

Abstract: A single-velocity-component Phase Doppler Particle Analyzer is used to survey and measure local variations in drop-size distributions and drop velocities in the near-nozzle region of a practical, contra-swirling, prefilming airblast atomizer. The technique of Laser Sheet Imaging is used to obtain global patterns of the spray. All measurements are taken with a constant pressure drop across the atomizer of 5 percent, at ambient air pressures of 1, 6 and 12 bar. The liquid employed is aviation kerosine at flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The effects of ambient pressure on the performance of atomizers have been investigated by some previous studies [14,19,20,36,42,43]. Jasuja [19] stated that mean velocity of spray droplets diminishes with increase in ambient pressure because this experiment keeps air-fuel mass ratio to be a constant so that at high ambient pressure, airflow velocity definitely will be smaller due to the increase of air density, and the airflow has less ability to scatter liquid sheets into droplets.…”
Section: Chapter 1 General Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of ambient pressure on the performance of atomizers have been investigated by some previous studies [14,19,20,36,42,43]. Jasuja [19] stated that mean velocity of spray droplets diminishes with increase in ambient pressure because this experiment keeps air-fuel mass ratio to be a constant so that at high ambient pressure, airflow velocity definitely will be smaller due to the increase of air density, and the airflow has less ability to scatter liquid sheets into droplets.…”
Section: Chapter 1 General Introductionmentioning
confidence: 99%
“…Leong et al [20] found that the increase in ambient pressure leads to the decrease of spray penetration depth when pressure drop and fuel flow rate are held constant. Zheng et al [42] used PDPA to measure droplet size distributions and droplet velocity of a prefilming airblast atomizer at different ambient pressures. The results showed that the effect of ambient pressure on the average size and velocity profiles of spray droplets is quite small.…”
Section: Chapter 1 General Introductionmentioning
confidence: 99%
See 1 more Smart Citation